THE MAIN EQUIPMENT BUSINESS OF WEAPON SYSTEMS (ALUTSISTA) IN DEFENSE: MARKET STRUCTURE AND COMPANY MERGER - Susdarwono, Endro Tri (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
Defense procurement is basically a strategic and sensitive issue. This involves detailed information regarding the national defense capacity and capability that other countries may not know as much as possible. This study aims to describe the business of the main weapon system (alutsista) in defense related to how the defense industry cycles, the character of the defense industry, market structure and company mergers. The approach in this study uses a descriptive approach, while the type of research is descriptive qualitative research. The defense industry, like any industry, undergoes a process of growth to mature. The defense industry has various characteristics that indicate its identification in terms of the defense economy. The market structure related to the practice of the defense industry is more emphasized on the imperfect market structure. In the defense industry, monopoly, oligopoly, and competitive markets are heavily influenced by internal and external factors of the company. In the commercial defense industry, there is an intention to combine two or more companies to minimize costs or maximize profits. Another reason for the merger of the two companies can also be related to the factors of production, and the specific objectives of the company.